Prevalence and Molecular Characterization of Cystic Echinococcosis in Livestock Population of the Malakand Division, Khyber Pakhtunkhwa, Pakistan - Khan, Jadoon; Basharat, Nosheen; Khan, Salman; Jamal, Syed Muhammad; Rahman, Sadeeq ur; Shah, Aamer Ali; Khan, Sanaullah; Ali, Rehman; Khan, Shahid Niaz; Ali, Ijaz (Frontiers in Veterinary Science, 2021)
Cystic Echinococcosis is a neglected zoonotic disease prevalent in Pakistan but, genetic diversity of the cestode is largely un-explored in Pakistan. This study investigated the molecular epidemiology of echinococcosis infecting the livestock population in Malakand Division, Khyber Pakhtunkhwa, Pakistan. A total of 1200 livestock including buffaloes, cattle, goats, and sheep were examined for echinococcosis from November 2017 to November 2018 at different slaughter houses in Malakand division. Hydatid cysts were collected from different organs and hydatid cyst fluid (HCF) was examined microscopically and was used for DNA extraction. The LSU (rrnl) and NAD1 genes were amplified and sequenced. The overall prevalence of cystic echinococcosis was 17% (204/1200), including cows (21.7%), buffaloes (17.4%), goats (10%) and sheep (9.6%). Although, the condition was relatively more prevalent among male (17%) than female (16.9%) and animals of older age group (>5 years) (p= 0.710). Liver (63.2%) and lungs (25%) were more affected as compared to kidneys (6.8%) and heart (4.9%). HCF analysis indicated that (52.0%) were sterile and (48.0%) were fertile cysts. Sequencing and phylogenetic analysis confirmed 80.0% of the isolates as Echinococcus granulosus sensu stricto (G1-G3) in all animal species, while Echinococcus equinus (G4) and Echinococcus ortleppi (G5) were present in buffaloes. The present study concluded that cystic echinococcosis is significantly higher in livestock population in Malakand. Besides, E. granulosus sensu stricto (G1-G3), the circulation of E. ortleppi genotype (G5) and E. equinus (G4) in livestock was also noted.